Dielectric spectroscopy of PVA-Ni0.5Zn0.5Fe2O4 polymer nanocomposite films. Issue 4 (1st October 2020) - Taha, T.A.; Hassona, A.; Elrabaie, S.; Attia, M.T.
ABSTRACT: This paper seeks to address the AC electrical properties of polyvinyl alcohol (PVA)-Ni0.5 Zn0.5 Fe2 O4 nanocomposites with different weight ratios (PVA/Ni0.5 Zn0.5 Fe2 O4 = 100/0, 95/5, 85/15, and 50/50) in the temperature ranging from 323 to 403 K at the frequencies from 0.01 Hz to 20 MHz. The real part of the complex permittivity (ԑʹ) was enhanced with both the temperature and concentration of Ni0.5 Zn0.5 Fe2 O4 nanocrystals, which originates from nano-capacitor structures experiencing interfacial polarization. These nanocomposites were shown to enhance the imaginary part (ԑ″) with the temperature, which was attributed to mobile charge carriers along conductive fillers. The static (ԑs ) and infinity (ԑ∞ ) permittivity were obtained from Cole–Cole plots and showed an increase with temperature. The relaxation time (τo ) and molecular relaxation time (τm ) showed temperature dependence and decrease with increasing the temperature. The Gibbs free energy (G), enthalpy (ΔH), and the entropy (ΔS) of the activation are estimated. The ac conductivity showed frequency and temperature dependence and the charge carrier transport follow correlated barrier hopping model (CBH). The Austin-Mott model was applied to the nanocomposites and showed that the density of states at the Fermi level increased with increasing the temperature.